Comparison of Traditional PWM and Phase Disposition PWM for a 5-Level Cascaded H-Bridge (CHB) Inverter in Low-Voltage Applications - Hassan, Mohd Khairy; Ahmad Zaidi, Ahmad Mazlan; Giserlerry, Brian Crisswill G; Jonly, Paran; Ponniran, Asmarashid; Abu Bakar, Afarulrazi (Journal of Electronic Voltage and Application, 2025)
Multilevel inverters play an important role in power systems as they provide better output waveform quality and help reduce harmonic distortion (THD). In this paper, a 5-level Cascaded H-Bridge (CHB) inverter is designed and tested using MATLAB Simulink. The inverter consists of two H-bridge cells, with each cell supplied by an equal DC voltage source. The 5-level configuration is chosen because it requires fewer switching devices compared to a 7-level inverter and is easier to implement, particularly for small low-voltage systems. Two modulation methods are used in this simulation. The first is Traditional PWM (TPWM), which employs one sine wave and one triangular carrier wave. The second is Phase Disposition PWM (PDPWM), where multiple triangular carriers are all in the same phase. Both PWM methods are tested under the same conditions, using a 50 Hz fundamental frequency to match the Malaysian power supply standard. To analyze the effect of filtering, the inverter is tested before and after applying a passive LC filter. Simulation results show that THD is reduced from 57.40% to 5.81% for TPWM, and from 27.38% to 1.83% for PDPWM after filtering. These results demonstrate that PDPWM is more effective when used with a passive filter. This work highlights the potential of PDPWM for applications in renewable energy systems, motor drives, and electric vehicles, and suggests opportunities for future exploration of advanced PWM strategies such as Modified PWM (MPWM) and AI-based modulation.